2001
DOI: 10.1115/1.1385835
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Study of Pressure Fluctuations Caused by Impeller-Diffuser Interaction in a Diffuser Pump Stage

Abstract: Two-dimensional and three-dimensional, unsteady state Reynolds-averaged Navier-Stokes (RANS) equations with standard k-ε turbulence models were solved within an entire stage of a diffuser pump to investigate pressure fluctuations due to the interaction between impeller and diffuser vanes. A complete solution of transient flows due to the interaction between components in the whole pump without approximating the blade count ratio of impeller to diffuser was obtained by employing an Arbitrary Sliding Mesh. The u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
51
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 113 publications
(54 citation statements)
references
References 18 publications
2
51
0
1
Order By: Relevance
“…First of all, a steady calculation should be achieved, and then the steady results are set as the initial boundary of the transient calculation; the absolute convergence criterion of transient calculation is that the residual is less than 1 × 10 −5 . In order to have enough resolution for the transient calculation, time step size Δ is set to 111.1 s. Thus, each impeller revolution is calculated in a time sequence of 360 time steps, which means that every time step the impeller revolves 1 degree [23]. And the convergence of transient calculation has a great influence on the results, so at least thirty periods have been computed for unsteady analysis to guarantee the numerical accuracy.…”
Section: Solution Parameters and Boundary Conditionsmentioning
confidence: 99%
“…First of all, a steady calculation should be achieved, and then the steady results are set as the initial boundary of the transient calculation; the absolute convergence criterion of transient calculation is that the residual is less than 1 × 10 −5 . In order to have enough resolution for the transient calculation, time step size Δ is set to 111.1 s. Thus, each impeller revolution is calculated in a time sequence of 360 time steps, which means that every time step the impeller revolves 1 degree [23]. And the convergence of transient calculation has a great influence on the results, so at least thirty periods have been computed for unsteady analysis to guarantee the numerical accuracy.…”
Section: Solution Parameters and Boundary Conditionsmentioning
confidence: 99%
“…The flow field entering the diffuser is unsteady and distorted, and it has a significant amount of kinetic energy to transfer to the static pressure. The pressure non-uniformity caused by the volute at the off-design condition further influences the flow fields in the diffuser Shi and Tsukamoto [17] in their study have shown that the Navier-Stokes code with the k-ε model is found to be capable of predicting pressure fluctuations in the diffuser. Sofiane et al [18] have carried out the numerical unsteady flow analysis in a vaned centrifugal fan.…”
Section: Introductionmentioning
confidence: 99%
“…The numerical simulation made by Heilmann and Siekmann [6] and Majidi and Siekmann [7] showed the strong secondary flow in volute and circular casings of centrifugal pumps. Ziegler et al [8], Shi and Tsukamoto [9], Shum et al [10], and Akhras et al [11] studied impeller diffuser interaction on the pump performance and showed that a strong pressure fluctuation is due to the unsteadiness of the flow shedding from impeller exit.…”
Section: Introduction:-mentioning
confidence: 99%